Neutrophil extracellular traps accelerate vascular smooth muscle cell proliferation via Akt/CDKN1b/TK1 accompanying with the occurrence of hypertension. Issue 10 (3rd October 2022) - Fang, Xinhui; Ma, Ling; Wang, Yanfu; Ren, Fang; Yu, Yanqiu; Yuan, Zhengwei; Wei, Hongquan; Zhang, Haipeng; Sun, Yingxian
Abstract : Objective: Neutrophil extracellular traps (NETs) can trigger pathological changes in vascular cells or vessel wall components, which are vascular pathological changes of hypertension. Therefore, we hypothesized that NETs would be associated with the occurrence of hypertension. Methods: To evaluate the relationship between NETs and hypertension, we evaluated both the NETs formation in spontaneously hypertensive rats (SHRs) and the blood pressure of mice injected phorbol-12-myristate-13-acetate (PMA) via the tail vein to induce NETs formation in arterial wall. Meanwhile, proliferation and cell cycle of vascular smooth muscle cells (VSMCs), which were co-cultured with NETs were assessed. In addition, the role of exosomes from VSMCs co-cultured with NETs on proliferation signaling delivery was assessed. Results: Formation of NETs increased in the arteries of SHR. PMA resulted in up-regulation expression of citrullinated Histone H3 (cit Histone H3, a NETs marker) in the arteries of mice accompanied with increasing of blood pressure. NET treatment significantly increased VSMCs count and accelerated G1/S transition in vitro . Cyclin-dependent kinase inhibitor 1b (CDKN1b) was down-regulated and Thymidine kinase 1 (TK1) was up-regulated in VSMCs. Exosomes from VSMCs co-cultured with NETs significantly accelerated the proliferation of VSMCs. TK1 was up-regulated in the exosomes from VSMCs co-cultured with NETs and in both the arterial wall and serum of mice with PMA. Conclusion: NETs promote VSMCs proliferation via Akt/CDKN1b/TK1 and is related to hypertension development. Exosomes from VSMCs co-cultured with NETs participate in transferring the proliferation signal. These results support the role of NETs in the development of hypertension. Abstract :